HYPERTENSION RISK FACTORS IN WORKERS AT THE DEPOK CITY SERVICE - Syafa'atur Rosidah; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Non-communicable diseases (NCDs) have become a health burden in developing countries like Indonesia. Hypertension is a public health threat because of its potential to cause complications such as stroke, coronary heart disease, and kidney failure. Various factors can cause Hypertension. This study aims to produce information about Hypertension's prevalence and risk factors. This study was conducted using secondary data sourced from the results of hypertension screening on workers at the Depok City Service. This study used a cross-sectional design study with a descriptive method. The unit of analysis in this study wAS workers who were at the Depok City Service with a sample of 280 respondents. Data was collected using SIPTM secondary data in 2022, obtained when there was a health screening in the Depok City Government Environment, and then analyzed descriptively. The results showed that the prevalence of blood pressure > 140/90 was 124 respondents (44.3%), 159 respondents (56.8%) were female, 51 respondents (18.2%) smoked, 120 respondents (42.9%) lack of physical activity (less than 30 minutes without stopping/day), 147 respondents (52.5%) lack of fruit and vegetable consumption, 73 respondents (26.1%) who consume excess salt (more than one teaspoon/day), 100 respondents (35.7%) consumed excess fat/oil (more than 5 tablespoons/day). Further research is needed to determine the relationship between risk factors and the incidence of Hypertension.